Optimum light conditions for eggs incubation and larval rearing of brown-marbled grouper Epinephelus fuscoguttatus - Mohammad Seth, Siti Nasihin; Nai, Han Tan; Rosli, Muhammad Khairulanwar; Mukai, Yukinori (2013)
Optimum light condition is important factor to reduce fish stress and to increase growth rate under cultivating conditions. There are many studies about light intensities for larval rearing. However, there are only few studies about light wavelengths and light intensities for egg incubation and larval rearing. Brown-marbled grouper, Epinephelus fuscoguttatus is an important fish species for aquaculture in Southeast Asia. This study was conducted to examine the optimum light wavelength and intensity for brown-marbled grouper using light emitting diode (LED) lamps. Brown-marbled grouper eggs were obtained from the IIUM hatchery. The eggs were incubated in 40L aquarium in dark rooms, using broad spectrum white light (430-460<λ<500-630 nm) as a control, blue light (450-485 nm), green light (500-560 nm), yellow light (580-605 nm) and red light (610-650 nm). The eggs were incubated under 0.38, 1.7 and 8.7 µmoles/m²/s for each wavelength. Each condition was conducted in triplicate. The temperature was maintained at 27.5-28.5oC. The larval rearing experiments were also conducted under the same conditions. Larvae were sampled to examine the survival rate and growth rate. Nannochlropsis were added from 0 days after hatching (density; 1million cells/ml). Feeding was started at one day old. Results showed that hatching rates had higher tendency under short wavelength lights (blue and green) and survival rates of larval rearing also had higher tendency under short wavelength lights.